The Role of Myth in Understanding Nature - Raymond Pierotti (Ethnobiology Letters, 2016)
Use of metaphor embodies myth in Western science and Native American traditional knowledge traditions about understanding the “natural” world and the nonhuman “other.” Using personal history, I compare a myth/metaphor from each intellectual tradition that shaped my thinking. Cultural trains of thought and metaphors impacted these myths and shaped my way of thinking. From Western scientific tradition, I examine the “Balance of Nature,” which dominated ecology and conservation biology from the 1850s until the 1990s. Balance and stability underlie major models in contemporary ecology and population biology, especially in wildlife and fisheries management. Before I trained as a Western style evolutionary ecologist, the myth of Wolf as creator figure in the traditions of Numic peoples (Shoshone, Comanche, Ute, Paiute) was the Indigenous creation myth that shaped my thinking. In the Balance of Nature, hidden metaphors are rooted in Western economic thought, specifically Capitalism. Similar metaphors in Numic peoples assume that humans are related ecologically to wolves, who served as teachers and guides. Stories, rather than data, served to fix these concepts into each cultural tradition. Although Numic beliefs appear “irrational” to Western society, they are more attuned to twenty-first century ecological and evolutionary thought than balance in nature, which lay at the root of Western ecological ideas until the 1980s. I discuss how my experiences with changing environmental conditions combined with my work with Indigenous peoples. Exposure to philosophical and empirical approaches from ethnobiology led me to explore these themes.